Rancang Bangun Alat Pengiris Singkong dengan Metode Quality Function Deployment (QFD): [Design and Development of a Cassava Slicing Tool using The Quality Function Deployment (QFD) Method] - Christiani, Agustina; Theresia, Jessica (Universitas Pelita Harapan, 2025)
This research was conducted to design and develop a cassava slicing tool for the UMKM (Micro, Small, and Medium Enterprises)